Improvement of the military classifier in the field of satellite navigation systems - Pryimak, Oles (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
Background. Satellite navigation systems (SNS) are in service and actively used by all branches of the military. With the sharp increase in the personnel of the Armed Forces of Ukraine (AFU), the variety of newly approved SNS has significantly increased, and changes in combat tactics have revealed issues related to the impracticality of using outdated models, their standardization, and the lack of a systematic approach to comparing their technical characteristics. The aim of this article is to create prerequisites for the systematization and comparison of already adopted SNS, as well as for further development of technical requirements for prospective models by improving the existing regulatory framework. M e t h o d s. In the process of writing the article, general scientific methods of analysis, comparison, synthesis, formal-legal methods, induction, and deduction were used to find solutions to the described problems. Methods of consolidation and clustering were used to group existing SNS samples by their usage method. The method of logical constructions was used to develop the conceptual apparatus. Results. The article proposes an improvement of the existing military classifier (MC) 001-2000 in the form of a draft classifier of satellite navigation systems for use in the AFU. The proposed suggestion is based on the successful path of standardization in the field of unmanned systems. The work discusses the problems of unifying the conceptual apparatus and proposes an approach to the systematization of SNS adopted and approved for use in the AFU. A strategy for implementing the proposed project is also presented. Conclusions. The approval of the SNS classifier will provide normative possibilities to develop clear standards and requirements for the technical characteristics of SNS, create an open competitive market environment, attract a wider range of developers, and find new or improve existing technological solutions, ultimately leading to qualitative technological growth in AFU provisioning. The conducted research has practical and theoretical value regarding the development of an SNS support strategy and justifying the need to decommission ineffective or outdated navigation devices.